Hubungan Dukungan Sosial dari Orangtua dengan Optimisme Karier Mahasiswa Tingkat Akhir - Munawija, Arli; Firman, Firman (ARZUSIN, 2024)
This research is motivated by the phenomenon where many final year students tend to lack career optimism, resulting in insufficient confidence in preparing for their careers after graduation. In Indonesia, issues related to career optimism have a significant impact on the unemployment rate. An individual's career optimism can be seen from self-confidence and perceptions of career opportunities. One of the factors suspected to influence career optimism is social support from parents. However, final year students often receive inadequate social support from their parents, which can affect their career optimism. The objectives of this study are to: (1) Describe the parental social support received by final year students regarding their careers, (2) Describe the career optimism of final year students, and (3) Examine the significant relationship between parental social support and career optimism among final year students. The type of research used is descriptive correlational quantitative. The research sample consisted of 287 final year students using purposive proportional random sampling technique. The instruments used were scales measuring parental social support and career optimism. Data were analyzed using descriptive analysis techniques and Pearson Product Moment correlation to determine the relationship between parental social support and career optimism among final year students. The results of the study revealed that: (1) The parental social support received by final year students is in the high category, (2) The career optimism of final year students is in the high category, and (3) There is a significant positive relationship between parental social support and career optimism among final year students with r = 0,244.